Red One [videorecording (DVD)] - Garcia, Hiram, 1976- (Amazon MGM Studios, 2025)
After Santa Claus Code Name: Red One is kidnapped, the North Pole's Head of Security must team up with the world's most infamous bounty hunter in a globe-trotting, action-packed mission to save Christmas.